Localization of Felis catus Papillomavirus Type 2 E6 and E7 RNA in Feline Cutaneous Squamous Cell Carcinoma. Issue 3 (May 2018) - Hoggard, Nathan; Munday, John S.; Luff, Jennifer
Findings from polymerase chain reaction–based methods have suggested a role of Felis catus papillomavirus 2 (FcaPV-2) in the development of feline cutaneous squamous cell carcinoma (SCC). However, because polymerase chain reaction cannot localize deoxyribonucleic acid or ribonucleic acid within the lesion, it is difficult to differentiate a coincidental FcaPV-2 infection and a causative association. Given that a key event in the pathogenesis of human papillomavirus–induced cancer is the expression of viral E6 and E7 oncogenes, localization of FcaPV-2 E6 and E7 transcription within neoplastic cells in feline SCCs would support a causative role for this papillomavirus. Therefore, RNAscope in situ hybridization was used to localize FcaPV-2 E6 and E7 transcripts in 18 formalin-fixed paraffin-embedded samples of cutaneous SCC. Positive signals were present within 5 of 9 samples (56%) from ultraviolet-protected sites and 0 of 9 samples from ultraviolet-exposed sites. In the 4 in situ hybridization–positive samples that contained adjacent hyperplastic skin, hybridization patterns in these regions were characterized by intense nuclear signals within the superficial epidermis and punctate signals within the basal epithelial layers. However, within the 5 SCCs, punctate signals were present within all layers of the epidermis, with progressive loss of intense nuclear signals within the superficial epidermis. This hybridization pattern is consistent with unregulated E6 and E7 transcription and decreased viral replication and is similar to the pattern observed in human papillomavirus–induced cancers as they progress from hyperplastic lesions containing productive infections to nonproductive neoplasms. These findings support a causative role for FcaPV-2 in the pathogenesis of feline SCC.